2021
DOI: 10.3389/fenvs.2021.691523
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Land-Energy-Water Nexus Models Across Scales: Progress, Gaps and Best Accessibility Practices

Abstract: Approaches that integrate feedback between climate, land, energy and water (CLEW) have progressed significantly in scope and complexity. The so-called nexus approaches have shown their usefulness in assessing strategies to achieve the Sustainable Development Goals in the contexts of increasing demands, resource scarcity, and climate change. However, most nexus analyses omit some important inter-linkages that could actually be addressed. The omissions often stem from technical and practical considerations, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…While several literature reviews compare nexus models and methods (Endo et al, 2017;Kaddoura and El Khatib, 2017;Albrecht et al, 2018;Dai et al, 2018;Liu et al, 2018;Zhang et al, 2018;Abdi et al, 2020;Endo et al, 2020;Stylianopoulou et al, 2020;Purwanto et al, 2021;Vinca et al, 2021) and while new models and methodologies are necessary to advance any discipline, we found that there is a lack of and a strong need for quantitative comparison, validation, and assessment of the suitability of the large number of existing and upcoming nexus models. A good summary from Vinca et al (2021) shows the range of methodologies across several nexus models. The methodological approaches differ in a range of ways, including types of linkages between sectors (hard linked vs. soft linked), optimization vs. simulations, number of sectors included, as well as both temporal and spatial scales (local, state/province, river basin, national, continental to global).…”
Section: Nexus Methodologiesmentioning
confidence: 93%
See 3 more Smart Citations
“…While several literature reviews compare nexus models and methods (Endo et al, 2017;Kaddoura and El Khatib, 2017;Albrecht et al, 2018;Dai et al, 2018;Liu et al, 2018;Zhang et al, 2018;Abdi et al, 2020;Endo et al, 2020;Stylianopoulou et al, 2020;Purwanto et al, 2021;Vinca et al, 2021) and while new models and methodologies are necessary to advance any discipline, we found that there is a lack of and a strong need for quantitative comparison, validation, and assessment of the suitability of the large number of existing and upcoming nexus models. A good summary from Vinca et al (2021) shows the range of methodologies across several nexus models. The methodological approaches differ in a range of ways, including types of linkages between sectors (hard linked vs. soft linked), optimization vs. simulations, number of sectors included, as well as both temporal and spatial scales (local, state/province, river basin, national, continental to global).…”
Section: Nexus Methodologiesmentioning
confidence: 93%
“…The large and growing body of nexus literature shows that integrated and holistic management of interconnected global systems is becoming critical as the pressures on our limited and shared resources increase (Canyon et al, 2015;Siri et al, 2016;Allen et al, 2019;Hameed et al, 2019;Mabhaudhi et al, 2019;Olawuyi, 2020;Zarei, 2020). Past reviews of nexus literature (Cremades et al, 2019;Johnson et al, 2019;Simpson and Jewitt, 2019;Opejin et al, 2020;van Gevelt, 2020;Vinca et al, 2021) raised some of the same points highlighted in this study, such as the need for applied case studies, the curation of standardized data, the categorization of appropriate models for different use-cases, a shift from analysis to implementation through policy and governance mechanisms, and integration with existing multi-sector frameworks such as the SDGs. The conclusions from this paper reiterate several of these past recommendations but, in addition, highlight a concern that the scope of the nexus discipline is increasing in complexity and ambiguity as the number of new methodologies and studies grows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The water-energy -ecosystem nexus (WEEN) is a focus of much research (Kuriqi et al, 2020;Vinca et al, 2021;Yadav et al, 2021). Hydropower is an important part of WEEN, which is interconnected and interdependent with other sectors of the nexus (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%